(untitled) (Journal of Environmental Microbiology and Toxicology, 2021)
The process of microbial molybdenum reduction to molybdenum blue precipitate is a biological phenomenon exploited in the bioremediation of molybdenum pollutant. This process is impacted by a change of the surrounding temperature. In general, to model the impact of small temperature ranges on the growth rate of microorganisms on substrates, several models are available. Arrhenius is one of the models and is very common because it has few parameters. An apparent activation energy based on the Arrhenius plot on the rate of molybdenum reduction by Pantoea sp. strain HMY-P4 is reported in this study. A linear plot of ln qmax against 1/T at the temperature range studied (25–40 oC) resulted in an activation energy value of 45.69 kJ per mol (95% Confidence Interval or C.I., 32.04 to 59.35). The plot also yields the Arrhenius frequency factor (A) which was calculated as 2.71 × 107 (95% C.I., 1.25 × 105 to 5.86 × 109). The corresponding Q10 value of 2, which represents a relative 10 ˚C increase in the surrounding temperature and a doubling of the reaction rate. The Q10 value of 1.82 (95% C.I., 1.52 to 2.18) and a theta value of 1.06 (95% C.I., 1.05 to 1.08) was calculated. The values obtained in this work are within the normal range for many biological processes.